2014
DOI: 10.1016/j.devcel.2014.10.020
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAcylation Prevents Aggregation of the Polycomb Group Repressor Polyhomeotic

Abstract: The glycosyltransferase Ogt adds O-linked N-Acetylglucosamine (O-GlcNAc) moieties to nuclear and cytosolic proteins. Drosophila embryos lacking Ogt protein arrest development with a remarkably specific Polycomb phenotype, arising from the failure to repress Polycomb target genes. The Polycomb protein Polyhomeotic (Ph), an Ogt substrate, forms large aggregates in the absence of O-GlcNAcylation both in vivo and in vitro. O-GlcNAcylation of a serine/threonine (S/T) stretch in Ph is critical to prevent nonproducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
150
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(162 citation statements)
references
References 52 publications
12
150
0
Order By: Relevance
“…We also observed no difference in H3 methylation in somatic fol- licular cells between these genotypes. These findings are reminiscent of ogt mutants, which also did not show any change in H3K27me3 levels despite the fact that OGT is essential for Ph function and proper development (6,7).…”
Section: Polytene Chromosomes Reveal Genome-wide Distribution Of Chromentioning
confidence: 50%
See 1 more Smart Citation
“…We also observed no difference in H3 methylation in somatic fol- licular cells between these genotypes. These findings are reminiscent of ogt mutants, which also did not show any change in H3K27me3 levels despite the fact that OGT is essential for Ph function and proper development (6,7).…”
Section: Polytene Chromosomes Reveal Genome-wide Distribution Of Chromentioning
confidence: 50%
“…Pc group member super sex combs (ogt/sxc) encodes the Drosophila O-GlcNAc transferase (OGT), which regulates Pc-mediated repression by post translationally O-GlcNAcylating and stabilizing Polyhomeotic (Ph), a member of PRC1 in Drosophila (6 -8). Ph forms large protein aggregates and cannot function in ogt mutants, leading to homeotic defects (7,9). Moreover, it has been shown that knockdown of mammalian OGT decreases H3K27me3 levels by affecting the stability of E(z) homolog 2 (EZH2) in the MCF7 breast cancer cell line (1).…”
mentioning
confidence: 99%
“…RGCs represent faterestricted progenitors, which generate neuronal and glial cell types in a tightly controlled sequential manner. Early RGCs directly produce nascent neurons or intermediate neuronal progenitor cells that In Drosophila, the PRC1 component PHC polymerizes via its SAM domain and assembles PcG complexes into Polycomb bodies [50], with an essential role in gene repression [51]. The loss of PHC function abolishes the more compact and higher inter-TAD interactions of polycomb associated TADs when compared to other domains, and it indicates that PHC could influence global chromatin packaging [52].…”
Section: Embryonic and Adult Neurogenesismentioning
confidence: 99%
“…TADs are highly conserved across different species and cell types [46,47], and segregate dependent on their association with the nuclear lamina, replication timing, histone signatures, and the transcriptional activity of the genes residing within a TAD [48,49]. In Drosophila, the PRC1 component PHC polymerizes via its SAM domain and assembles PcG complexes into Polycomb bodies [50], with an essential role in gene repression [51]. The loss of PHC function abolishes the more compact and higher inter-TAD interactions of polycomb associated TADs when compared to other domains, and it indicates that PHC could influence global chromatin packaging [52].…”
Section: Polycomb Group Complexes Regulate Chromatin At Different Scalesmentioning
confidence: 99%
“…SAM domains of PH proteins can form a helical polymer [75]. Mutation of a single amino acid in the SAM domain, which blocks polymerization, ruins the repressor capabilities of PH protein [76]. SAM domain polymerization is essential for the in vivo growth suppressive function of PH too [77].…”
Section: Evolutionarily Conserved Domains In Pcg Proteinsmentioning
confidence: 99%